MEMORABLE TOURIST EXPERIENCE: KUNJUNGAN WISATA KE SENTRA PRODUKSI EMPING MELINJO SEBAGAI DAYA TARIK WISATA HERITAGE - Sri Fajar Ayuningsih; Nurbaeti Nurbaeti; Jajang Gunawijaya (Jurnal Hospitality dan Pariwisata, 2023)
The tourist experience is one of the critical success factors in the tourism industry. Every destination, tourist attraction, and other tourism product must be able to provide a memorable tourist experience.  Banyuresmi tourism village, Pandeglang, Banten has the potential to attract cultural heritage tourism, including gastronomic tourism. However, the potential has not been developed as a tourist attraction that can provide a memorable experience for tourists. This descriptive qualitative research aims to identify and analyze the potential of cultural and gastronomic tourism that is memorable for tourists. Primary data collection was obtained from field observations and in-depth interviews with key informants. Data analysis through a reduction process to determine the components that provide a memorable experience for travelers. The results of the study indicate that cultural and gastronomic tourism experiences that are memorable for tourists when visiting Banyuresmi tourism village can be formed from five components, namely; (1) good social interaction between residents and tourists, (2) camping activities provide a memorable experience because they have local authenticity, (3) good service and hospitality of residents become a special attraction and give a deep impression to tourists, (4) the tradition of camping and making bamboo crafts becomes an impressive cultural and gastronomic tourism attraction for tourists, and (5) challenges encountered along the way to the location also create an unforgettable experience for tourists.